Randomized trial of BCG in healthcare workers to reduce absenteeism during the COVID-19 pandemic in sub-Saharan Africa - Silva, I (2024)
© The Author(s) 2024. Published by Oxford University Press on behalf of Royal Society of Tropical Medicine and Hygiene.